Proses Eksekusi Putusan Pengadilan Berkaitan Kewenangan Penyadapan Oleh Kejaksaan Republik Indonesia - Hendra Dinatha (Jurnal Penelitian Hukum Legalitas, 2021)
The pros and cons of the dissolution of civil society organizations have been an ongoing issue since the emergence of Law Number 16 of 2017 concerning Social Organizations, where there was a debate about how these Community Organizations should be dissolved. The approach method used in this research is the method of juridical analysis approach. With the research specifications used in this research is descriptive analytical. Legal data materials obtained from both the literature and field research were analyzed qualitatively, namely the data analysis method by conducting a selection of the data obtained based on their quality and truth and those related to the problems to be discussed. Based on the results of the study, it was found that the authority of the Ministry of Home Affairs in the mechanism for dissolution of communityt organizations in Indonesia is based on Law Number 16 of 2017 concerning Stipulation of Government Regulation in Lieu of Law Number 2 of 2017 concerning Amendments to Law Number 17 of 2013 concerning Community Organizations into Law, Article 62 which explains that for Community Or[1]ganizations committing violations given a written warning once within seven working days from the date the warning was issued. In the event that the Community Organizations does not comply with the written warning within a predetermined period of time, the Minister who carries out government affairs in the fields of law and human rights in accordance with his authority shall impose sanctions on the termination of activities.